Hypercalcemia of Malignancy in Thymic Carcinoma: Evolving Mechanisms of Hypercalcemia and Targeted Therapies - Cheng Cheng; Jose Kuzhively; Sanford Baim (Case Reports in Endocrinology)
Here we describe, to our knowledge, the first case where an evolution of mechanisms responsible for hypercalcemia occurred in undifferentiated thymic carcinoma and discuss specific management strategies for hypercalcemia of malignancy (HCM). Case Description. We report a 26-year-old male with newly diagnosed undifferentiated thymic carcinoma associated with HCM. Osteolytic metastasis-related hypercalcemia was presumed to be the etiology of hypercalcemia that responded to intravenous hydration and bisphosphonate therapy. Subsequently, refractory hypercalcemia persisted despite the administration of bisphosphonates and denosumab indicative of refractory hypercalcemia. Elevated 1,25-dihydroxyvitamin D was noted from the second admission with hypercalcemia responding to glucocorticoid administration. A subsequent PTHrP was also elevated, further supporting multiple mechanistic evolution of HCM. The different mechanisms of HCM are summarized with the role of tailoring therapies based on the particular mechanism underlying hypercalcemia discussed. Conclusion. Our case illustrates the importance of a comprehensive initial evaluation and reevaluation of all identifiable mechanisms of HCM, especially in the setting of recurrent and refractory hypercalcemia. Knowledge of the known and possible evolution of the underlying mechanisms for HCM is important for application of specific therapies that target those mechanisms. Specific targeting therapies to the underlying mechanisms for HCM could positively affect patient outcomes.